Hubungan Religiusitas dan Kesepian pada Mahasiswa Baru yang Berasal dari Luar Daerah - Marisya Pratiwi; Sri Fatmawati Mashoedi (Fakultas Psikologi Universitas Pancasila, 2011)
The study aims to examine religiosity, loneliness and the relationship between the two conditions on freshmen studying outside their home town. The respondents are 259 Moslem freshmen who are studying at the University of Indonesia and come from outside greater Jakarta. The study uses religiosity scale which is adapted from religiosity dimensions developed by Glock and Stark (1966) and UCLA Loneliness Scale Revised developed by Russel (1980). The main result shows a significant negative relationship between religiosity and loneliness (r= -0.341, p<0.05).